Response to mutation and variants of the SARS-CoV-2 gene - Parwanto, M.L. Edy (Universa Medicina, 2021)
Since the COVID-19 pandemic, our society has come to understand that the cause is the Corona Virus (2019-nCoV) or more popularly known as the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Â It has become a reality that as a result of the COVID-19 pandemic, many people have died. We need to record new cases of COVID-19 in other countries, namely the UK and Germany at the end of 2020. This needs to be conveyed because both countries are showing high new cases of COVID-19. The high number of new cases of COVID-19 in the UK and Germany is thought to be related with gene mutation that resulted new strain of SARS-CoV-2. It has been reported in the UK on December 2020 that SARS-CoV-2 gene mutations resulted in a new variant called VUI-202012/01 (Variant Under Investigation, year 2020, month 12, variant 01). The British government implemented new lockdowns for England and Scotland to deal with the spread of the new VUI-202012/01 variant of SARS-CoV-2. Recent news reports that the Government of Germany is extending lockdowns on its territory until January 31th 2021. The policy regarding the prohibition of foreigners entering Indonesia in relation to the emergence of a new variant of the corona virus in the UK is regulated in the Indonesia COVID-19 Task Force Circular Letter No.4 2020. Temporary entry restriction for Foreigners to Indonesia 1-14 january 2021.Â Â